Genetic diversity of clinical and environmental strains of Salmonella enterica serotype Weltevreden isolated in Malaysia. - Thong, Kwai Lin; Goh, Y.L.; Radu, S.; Noorzaleha, S.; Yasin, R.; Koh, Y.T.; Lim, V.K.E.; Rusul, G.; Puthucheary, S.D. (American Society for Microbiology, 2002)
The incidence of food-borne salmonellosis due to Salmonella enterica serotype Weltevreden is reported to be on the increase in Malaysia. The pulsed-field gel electrophoresis (PFGE) subtyping method was used to assess the extent of genetic diversity and clonality of Salmonella serotype Weltevreden strains from humans and the environment. PFGE of XbaI-digested chromosomal DNA from 95 strains of Salmonella serotype Weltevreden gave 39 distinct profiles with a wide range of Dice coefficients (0.27 to 1.00), indicating that PFGE is very discriminative and that multiple clones of Salmonella serotype Weltevreden exist among clinical and environmental isolates. Strains of one dominant pulsotype (pulsotype X1/X2) appeared to be endemic in this region, as they were consistently recovered from humans with salmonellosis between 1996 and 2001 and from raw vegetables. In addition, the sharing of similar PFGE profiles among isolates from humans, vegetables, and beef provides indirect evidence of the possible transmission of salmonellosis from contaminated raw vegetables and meat to humans. Furthermore, the recurrence of PFGE profile X21 among isolates found in samples of vegetables from one wet market indicated the persistence of this clone. The environment in the wet markets may represent a major source of cross-contamination of vegetables with Salmonella serotype Weltevreden. Antibiotic sensitivity tests showed that the clinical isolates of Salmonella serotype Weltevreden remained drug sensitive but that the vegetable isolates were resistant to at least two antibiotics. To the best of our knowledge, this is the first study to compare clinical and environmental isolates of Salmonella serotype Weltevreden in Malaysia.